Re: reciprocals — Their internal constitution and external distribution - den Dikken, Marcel (Nordlyd, 2026)
In languages that have nominal reciprocals, these expressions exhibit morphosyntactic variation. This paper provides a detailed perspective on the range of this variation with the aid of a syntactic analysis that takes the composition of these expressions seriously, modelling their internal structure in the form of a syntax that assigns discrete structural positions to their component parts. In reciprocals juxtaposing a numeral and an alterity word (such as English one another), the numeral occupies the specifier and the ‘other’ part sits in the complement position of a head (overt in PPs, silent elsewhere) that mediates the relationship between the two. Reciprocal pronominals with this Spec–Head–Complement structure are barred from serving as direct arguments of verbs, being construed instead as asyndetic specifiers of a SE clitic pronoun.
Keywords: anaphor; nominal reciprocal; specificational asyndetic coordination; case; agreement